A new methodology to determine the importance of game attributes. - Ernesto Pacheco-Velazquez; Virginia Rodes-Paragarino; Lucia Rabago-Mayer; Andre Bester (Serious Games Society, 2024)
Information and communication technologies have brought about a revolution in how we perceive, interpret, and learn. This ever-changing landscape presents both challenges and opportunities for enhancing students' learning experiences through innovative tools and strategies. One such strategies is collaboration and serious games into teaching, offering safe environments to solve real-world problems, improve comprehension and knowledge acquisition, develop technology skills, foster cooperation and collaboration, and provide an engaging and interactive learning experience. However, the development of effective simulation games requires careful consideration of various factors, including aesthetics, interface, gameplay, learnability, feedback, challenge, immersion, and game design, to name just a few. Evaluating simulation games poses a challenge due to interdisciplinary involvement and the lack of standardized methodology. This article proposes a methodological approach to assess the attributes of simulation games, providing valuable insights for informed decision-making regarding their design, improvement, effectiveness, and challenges in the realm of serious games.